Penerapan Metode Jigsaw dengan Integrasi Barcode untuk Meningkatkan Keaktifan Siswa SMA Negeri 9 Semarang - Eliyani Nur Khofifah; Suneki, Sri (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2024)
This research is motivated by the importance of the teacher's role in determining and applying effective learning methods so that students can actively participate in Civics learning. The results showed that teachers who used the lecture method which was too dominant resulted in students being less actively involved in the learning process. As a result, this research offers the jigsaw cooperative learning method integrated with barcodes as a solution to increase student activeness. In this way, students will better understand the material, work together in groups, and teach others. The integration of barcodes makes learning easier for students, they can scan barcodes connected to various websites. According to the results of the study, the percentage of student learning activity increased significantly from 60.8% before the study, then increased in cycle I obtained 69.8% and again reached an increase of 80.4% in cycle II. Keywords: student activity, learning methods, use of technology